Judgmental Biases of Individuals with a Fear of Blushing: The Role of Relatively Strict Social Norms. (20th May 2015) - Dijk, Corine; de Jong, Peter J.; Peters, Madelon L.
Abstract : Blushing‐fearful individuals often expect that others will judge them negatively. In two studies, we tested if this could be explained by having relatively strict beliefs about what is appropriate social behaviour. Study 1 used a student sample ( n = 74), whereas study 2 compared a clinical treatment‐seeking sample of blushing‐fearful individuals ( n = 33) with a non‐anxious control group ( n = 31). In both studies, participants were asked to read descriptions of common behaviours that could be considered as breaching the prevailing social norms but not necessarily so. Participants indicated (i) to what extent they considered these behaviours as violating the prevailing norm and (ii) their expectation of observers' judgments. Study 1 showed that strict norms were indeed related to fear of blushing and that the tendency of fearful participants to expect negative judgments could at least partly explain this relationship. Study 2 showed that high‐fearful and low‐fearful individuals do indeed differ in the strictness of their norms and that especially the norms that individuals apply to themselves might be relevant. These findings may provide fresh clues for improving available treatment options. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Messages: Blushing‐fearful individuals attribute relatively strict social norms to other people about which behaviours are appropriate and which are not and have stricter personal norms as well. Blushing‐fearful individuals' tendency to expect overly negative judgments in ambivalent social situations can partly be explained by their relatively strict social norms. Having relatively strict social norms may (also) explain why blushing-fearful individuals report to blush often and intensely. It may be worthwhile to address strict social norms in therapy for fear of blushing.